2020
DOI: 10.3390/rs12183030
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of UAV Altitude on Extracted Biophysical Parameters of Young Oil Palm

Abstract: The information on biophysical parameters—such as height, crown area, and vegetation indices such as the normalized difference vegetation index (NDVI) and normalized difference red edge index (NDRE)—are useful to monitor health conditions and the growth of oil palm trees in precision agriculture practices. The use of multispectral sensors mounted on unmanned aerial vehicles (UAV) provides high spatio-temporal resolution data to study plant health. However, the influence of UAV altitude when extracting biophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, the flight time at 70 m is significantly less than the flight time at the other two altitudes, with only 17.56 minutes compared to 45.35 minutes at 35 m and 42.47 minutes at 45 m ( Table 1 ). Similar results were reported by Avtar et al [ 56 ], who found that (1) the CA derived at flight altitudes of 20 m, 60 m, and 80 m yields a similar correlation with the ground truth of young oil palm ( Elaeis guineensis ); (2) tree heights derived from 60 m and 80 m flights showed slightly higher correlations with ground truth data than those derived from the 20 m flight altitude. Moreover, Sadeghi and Sohrabi [ 57 ] found that a higher flight altitude (80-140 m) yielded more accurate height measurements than a lower flight altitude.…”
Section: Discussionsupporting
confidence: 88%
“…However, the flight time at 70 m is significantly less than the flight time at the other two altitudes, with only 17.56 minutes compared to 45.35 minutes at 35 m and 42.47 minutes at 45 m ( Table 1 ). Similar results were reported by Avtar et al [ 56 ], who found that (1) the CA derived at flight altitudes of 20 m, 60 m, and 80 m yields a similar correlation with the ground truth of young oil palm ( Elaeis guineensis ); (2) tree heights derived from 60 m and 80 m flights showed slightly higher correlations with ground truth data than those derived from the 20 m flight altitude. Moreover, Sadeghi and Sohrabi [ 57 ] found that a higher flight altitude (80-140 m) yielded more accurate height measurements than a lower flight altitude.…”
Section: Discussionsupporting
confidence: 88%
“…Using high-resolution (3.94 cm) UAV multispectral imagery and ML algorithms, a probabilistic classification model was built to detect potential infections in Phoenix canariensis. The spatial resolution was achieved with 60 m altitude drone flights, an optimal flight altitude that has been proven to enhance the biophysical parameters extraction of vegetation [67]. This approach represents the first attempt to identify and detect possible infections on a palm tree scale in the Canary Islands based on spectral response.…”
Section: Discussionmentioning
confidence: 99%
“…The 90 × 90 overlaps added a high level of detail to the DEMs, and when compared with traditional topographic methods, these overlap levels were considered inferior. High levels of detail combined with an altitude reduction were reported by Avtar et al [50], who evaluated different flight heights for biophysical analysis of palm trees, and the authors observed a significant contribution of lower altitudes to an increase in errors. This result was attributed to the high level of detail in the image.…”
Section: Precision Of Digital Surface Modelsmentioning
confidence: 98%